Many-to-One Pursuit-Evasion Differential Game Method for UAVs Using Sequential Convex Programming - Tang, Haonan; Chen, Gong; Bai, Chengchao; Guo, Jifeng (Proceedings of ... IEEE International Conference on Unmanned Systems (Online), 2023)
Aiming at the many-to-one pursuit-evasion game problem for fixed-wing unmanned aerial vehicles (UAVs) with complete kinematic constraints, this paper proposes a sequential convex programming-based differential game method for UAVs. The method decouples the coupled pursuit-evasion differential game problem into several differential game subproblems and transforms the non-convex escape objective function into an anti-capture constraint. Linearization is used to convexify the constraint, and then the penalty function method is leveraged to transform the constraint into a convex constraint penalty function. Consequently, the differential game subproblems are transformed into multiple sequence convex programming problems so that the approximate saddle-point solutions can be efficiently and quickly solved. The simulation experiment is conducted in a three-to-one pursuit-evasion game scenario, and the results demonstrate the effectiveness of the proposed method.